Strategi Komunikasi Dalam Advokasi Hasil Penelitian (Studi: Mahasiswa Klinik Hukum Anti Korupsi Fakultas Hukum UNPAD Tahun 2014) - Atnan, Nur (UI Scholars Hub, 2015)
Contribution of Anti Corruption Legal Clinic of Faculty of Law Unpad is making change through research report‟s advocacy. Advocacy aimed to give more advamtage and meaning to the research conducted by the students. However by the observation of the writer, research report‟s advocacy in 2014 has not give significant support to the expexted changes. Writer interested to take research in this activity to analyse communication strategy in research report‟s advocacy. Research conducted by qualitative method through interview and researcher involved in every students‟ activity. Research shows that the main components in communication strategy in advocacy are communication planning, actuating and evalution. Yet, the evaluation has not conducted to the maxiumum effort.